PEMENUHAN KEBUTUHAN DASAR PADA LANSIA MENINGKATKAN KUALITAS HIDUP DI JAKARTA SELATAN - Yusriana Yusriana; Etty Rekawati; Dwi Nurviyandari (JURNAL KESEHATAN MERCUSUAR, 2018)
The decrease function and ability of the older people’s body make the fulfillment of basic needs in adequate. It causes decrease in quality of life. When the older people’s feels perceived physical weakness as limitation, so the perception of health will decrease too. This study aimed to identify the correlation fulfillment of bacic need with older people’s quality of life in Srengseng Sawah South Jakarta. Analytic correlation was used as design of this research with cross sectional study approach. This study used 111 samples, where as purposive sampling is applied in sample collection. In multivariate, paired linear regression is used to know characteristics confounding. The result were age (median=67,00), sex is women 84 person (75,7%) and buttom income 79 person (71,2%) as confounding with p value 0.00 for age, sex with p value 0.057 and p value for income 0.130. There is correlation with fulfillment of basic needs and quality of life in older people’s. This study suggest to increase quality of life in weakness or physical decrease in older people’s by over whelming the symptoms and positive improvement of older people’s perception.